Factors Affecting Job Satisfaction among Teachers of Some Selected Senior High Schools in Accra - Nutsuklo, P.A (University of Ghana, 2015)
This study attempts to find out the factors that affect job satisfaction of teachers of some selected senior high schools in Accra, Ghana. A cross-sectional design was used to collect data. Simple random sampling was used to select the population, and stratified sampling was used to select the respondents from each of the schools according to the various departments. A total of 155 questionnaires were administered to teachers of three selected senior high schools but 120 questionnaires were returned fully and appropriately filled. The study made use of both descriptive and inferential statistics such as frequencies, means, and standard deviation, including tindependent test and one-way Analysis of Variance (ANOVA) to obtain results. The overall level of job satisfaction of the teachers is low. Low level of salaries and poor conditions of service are the main causes of dissatisfaction of teachers in the selected senior high schools. It is also recommended that Ghana Education Service (GES) should improve and implement the conditions of service of teachers.
Thesis(M.A)-University of Ghana, 2015
Keywords: Job Satisfaction; Teachers; Senior High Schools